Program development and evaluation of a health equity education for undergraduate medical students in Japan: a pre–post study design - Tamaki Urban; Koki Yokota (Medical Education Online, 2025)
Sexual and gender minority (SGM) individuals in Japan experience significant health disparities. While Western curricula devote multiple hours to structured SGM health modules, Japanese medical schools offer only about 1 h, leaving future providers underprepared. This study aims to 1) develop a health equity education program on SGM for medical undergraduates in Japan, 2) assess the program’s effects while considering empathy levels and SGM identities, and 3) evaluate participant satisfaction with the program. A 3-h educational program was integrated into a psychology course for undergraduate freshmen within the faculty of medicine. Utilizing a pretest-posttest single-group design, the study evaluated outcomes through validated self-report measures and a satisfaction survey. ANOVA models examined the program effects on the awareness of inequities faced by SGM groups and attitudes towards them, while considering the moderating roles of empathy and SGM identities. Descriptive statistics examined program satisfaction. Among 112 participants (mean age 18.5 years, SD = 0.6), 2.7% identified as SGM, with 15.2% unsure. Awareness of SGM health disparities significantly increased from pre to postintervention (p < .001). Interaction analyses showed that this gain did not vary with empathy level (p = .286) or with SGM identity status (p = .445). Attitudes toward SGM individuals likewise improved (p < .001). Interaction analyses showed that this gain did not vary with empathy level (p = .699) or by identity (p = .414). Overall, 99.1% of participants reported satisfaction with the program, and all recognized its utility. The program appeared beneficial even for students who had not yet developed high levels of empathy or those with diverse identities. Our findings call for a sustained effort to embed such education within medical training programs, ensuring that future healthcare professionals are well-equipped to provide inclusive care to SGM individuals.